IMPROVING DISASTER PREPAREDNESS THROUGH WETLAND CONSERVATION - Dwina, Irma (International Conference On Social Science Education, 2023)
This research aims to analyze how wetland conservation can increase preparedness in facing natural disasters. A natural disaster is defined as a disaster caused by nature itself. Disaster preparedness is an important aspect as an effort to protect the environment and society, especially in wetland ecosystems. This research uses a qualitative approach with descriptive methods. Data collection techniques use literature studies. Data sources come from scientific journals, books, scientific essays, and literature related to the topic of discussion. Data was collected to identify and analyze the concrete role of wetlands, especially in mitigating natural disasters. The research results show that wetlands function as natural reservoirs that are able to absorb excess water in the flood season and supply water in the dry season. Vegetation in wetlands can also reduce the intensity of landslides. Wetland conservation programs that involve local communities and stakeholders in improving disaster preparedness can be the key to the success of wetland ecosystems. In line with this, ecosystem management education and training is also an important factor in increasing public awareness regarding the importance of managing wetlands as a means of mitigating disasters and maintaining environmental sustainability.